Predicting risk and outcomes for frail older adults: results of an umbrella review of available screening tools for frailty. Issue 4 (December 2016) - Apóstolo, J.; Bobrowicz-Campos, E.; Holland, C.; Cooke, R.; Santana, S.; Marcucci, M.; Vollenbroek, M.; Germini, F.; Cano, A.
Abstract : Background: Frailty is an age-related state of high vulnerability to adverse health outcomes after a stressor event, predisposing individuals to progressive decline in different functional domains and contributing to the onset of geriatric syndromes. Several assessment tools had their psychometric properties analysed in different systematic reviews (SRs). This study syntheses the existing evidence through an umbrella review (UR), developed within the context of the project "664367/FOCUS" funded under the European Union's Health Programme (2014–2020). Objective: To summarize the best available evidence from SRs on available measures to identify frailty in older adults, focusing on (i) their reliability, validity, and diagnostic accuracy in detecting the frail condition; (ii) their ability to predict adverse health outcomes. Methods: The review process was based on Joanna Briggs Institute procedures regarding URs. The studies considered as eligible for inclusion were quantitative SRs including older adults aged 60 years or more, recruited from any type of setting (primary care, long-term residential care, hospitals). The index tests were currently available screening tools for frailty in older adults. In addition, frailty indicators were considered. Tests from the Cardiovascular Health Study and the Canadian Study of Health and Aging, as well as other recognised gold standards were used as reference tests. Diagnosis of interest was frailty. Databases were searched from January 2001 to October 2015. Results: 10 SRs were appraised for methodological quality, and 6 SRs describing 25 screening tools and 7 frailty indicators were included. Based on evidence regarding capacity to detect frail condition, gait speed, Screening Letter, Timed get-up-and-go Test and PRISMA 7 appeared as potentially relevant for screening for frailty in a primary care setting. Tilburg Frailty Indicator was revealed to be the most reliable and valid measure (acceptable internal consistency, inter-rater reliability and concomitant validity). Frailty Index and two frailty indicators (gait speed and physical activity) were shown to be the most powerful predictors of future adverse health outcomes. Discussion: The most frequent limitations of 10 SRs were related to inappropriate definition of inclusion criteria, lack of a reference standard and lack of, or inappropriate tool used for critical appraisal of the included studies. In addition, lack of uniformity of provided statistics, and inconsistency in conferring significance to obtained results were observed. Almost all frailty indicators (with exception of gait speed) were not operationalized. Evidence compiled by this UR suggests that gait speed is the only measure that is sufficiently sensitive to identify frailty in older adults and, simultaneously, sufficiently accurate to predict increased risk of adverse outcome. However, because of limited specificity, its use in routine care should be accompanied by other instruments. Conclusion: The evidence showed that none of the analysed index tests has enough quality to be used as a single screening tool. There is a need for user-friendly instruments to identify frailty in older adults. Regarding predictive ability, Frailty Index, gait speed and physical activity can be used as single measures. Future studies focused on instruments for frailty should be more rigorous on methodology to improve the quality of obtained evidence.